Accreditation and assessment: What you need to know! - Frederick Burrack (Academic Chairpersons Conference Proceedings, 2022)
For many academic leaders, preparing for and successfully addressing accreditation expectations can be challenging. In this interactive session, a panel of representatives from multiple disciplines will provide advice and answer questions on how to prepare for and address accreditation expectations. Panel participants will be selected from assessment directors and program directors with successful experience in a variety of accreditation situations. Session participants will be invited to ask questions specific to their academic situations enabling the panel to provide insights toward a successful accreditation experience.
Keywords: accreditation; assessment; reporting; student achievement; academic excellence; program improvement